The Intelligent Mind - Winfield, Richard Dien. author. aut Link
X, 265 p.
Keywords: The Intelligent Mind conceives the psychological reality of thought and language, explaining how intelligence develops from intuition to representation and then to linguistic interaction and thinking. Overcoming the prevailing dogmas regarding how discursive reason emerges, this book secures the psychological possibility of the philosophy of mind.